Augmented Reality Technology Untuk Pengenalan Alat Transportasi Pada Anak Usia Dini (Studi Kasus KB Islam Terpadu Wildani 2 Surabaya) - Desi Rully Wahyuni; Nia Saurina; Nonot Wisnu Karyanto (Informatics Engineering Department-UWKS, 2016)
Wildani 2 is Moslem pre elementary school in Surabaya is one school for early childhood. In these schools, early childhood begin an introduction to the environment. Know the tools of transportation is one of KB IT curriculum Wildani 2 Surabaya. Media books with pictures of a 2-dimensional learning aids are used in familiar means of transportation. The media sometimes makes them bored, they often chat with classmates and teachers who are not paying attention to the theory. Therefore, researchers using augmented reality as one of the tools to learn about transportation. Learning aids using augmented reality is expected to attract interest in learning, fosters self-contained nature and add insight to early childhood. This is evidenced by the% of students in kbit Wildani 2 Surabaya can mention and repeat the spelling of the name in the Indonesian transport and 80% of students can mention and repeat the name in English means of transportation which demonstrate with augmented reality.